The unidirectional flagellum of R. sphaeroides : cloning and analysis of genes encoding regulatory, structural and motor components - Goodfellow, Ian Gordon (1996)
In this study several components responsible for the formation and function of the unidirectional flagellum of R. sphaeroides WS8 were identified via the characterisation of motility impaired TnphoA mutants. The role of the alternative sigma factor sigma 54 in flagellar gene regulation was also examined. Mutant M18 was defective in a fliI homologue, characterisation of this mutant revealed that FliI is not essential for flagellar formation in R. sphaeroides. This differs from that reported in the literature for S. typhimurium and so highlights the importance of studying R. sphaeroides as a model for flagellar motility. Analysis of another mutant Nm7 revealed that it was defective in FliF, a rotor component around which other flagellar components assemble. Overexpression of a FliF fusion protein allowed the production of anti FliF antiserum. DNA sequencing upstream and downstream of the fliF gene, revealed several other genes encoding flagellar components and a potential flagellar gene regulator (Torf). fliE, encoding a component of the basal body of unknown function, was identified upstream of fliF, an interposon mutant was created and was unable to be complemented by the wild type gene in trans suggesting a dominant effect. This is the first dominant mutation to be isolated in any fliE . The gene encoding the motor component FliG was also identified downstream of fliF and its C-terminal motility domain was found to contain regions that are conserved between FliG proteins from unidirectional and bidirectional motors, these may play a role in motor rotation and not switching. An overexpressed poly histidine FliG fusion protein was found to form a complex with the FliF-GST fusion protein ill vitro. The torf gene encodes a protein with homology to sigma 54 enhancer binding proteins. The Torf protein lacks any obvious DNA binding motif and may represent a novel member of the sigma 54 enhancer binding protein family.